Preparation of Colloidal Silica Solution in Various Electromagnetic Fields and Investigation of the Colloidal Solution’s Molecular Structure and Optical Properties - AL-Sharuee, Israa F.; Mohammed, Ruaa A. (MĀPAN : journal of Metrology Society of India, 2025)
Specifically, the process of creating the particles using a modified sol-gel method and synthesizing them in a uniform, non-dispersed form was the focus of the investigation. The synthesis of silica nanoparticles, which are particles with a diameter of less than 20 nanometers, was the subject of the study. In the course of the numerous condensation processes that take place in the silica solution, the processes of organizing particles through the magnetic field integration mechanism are powerful and possess a particular energy. It is dependent on the method that is used to modify the pH, the intensity of the magnetic field, and also the time that will affect the length of exposure of the distributed silica nanoparticles particularly. This is because it will be feasible to correctly control the size of these particles in the future. The outcome will depend on how these elements change. By using it, the size of the nanoparticles that have been prepared can either be decreased or raised, depending on the capacity of the material that has been prepared. Through the utilization of dynamic light scattering, an investigation into the relationship between the magnetic field and the size and distribution of silica particles is being taken. Because of the process that influences the introduction of particles into production, medical, military, or other applications depending on the materials that are utilized, this study will be important in the future for modifying the size of particles and their many applications.